De la cámara oscura a la cinematografía: tres siglos de tecnología al servicio de la creación visual - Frutos Esteban, Francisco Javier (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2008)
The camera obscura, as a guiding image of optics and the germ of a whole world of media that have revolutionised human perception, has now emerged as a fundamental element in the ever growing development of the sciences of observation. From the 17th to the 20th centuries, technologies that were heir to the camera obscura, such as photography, stereoscopy, chronophotography and cinematography have explored, represented and constructed new worlds –both physical and metaphysical, real and imagined- that were inaccessible to the naked eye.